2014
DOI: 10.1080/09669582.2014.902065
|View full text |Cite
|
Sign up to set email alerts
|

Motivation-based transformative learning and potential volunteer tourists: facilitating more sustainable outcomes

Abstract: Transformative learning (TL) is an important component of sustainable volunteer tourism experiences, potentially reducing unsustainable outcomes, and educating and enlightening volunteers. This paper reviews theories and issues about TL in volunteer tourism, and analyzes data from 1008 useable responses to an online survey of potential volunteer tourists. A factor-cluster analysis of potential volunteer tourists' motivations identified key volunteer tourist segments and assessed differences in expectations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 60 publications
3
42
0
2
Order By: Relevance
“…In recent years, tourism has gradually gained recognition as a learning path (Coghlan & Gooch, 2011;Falk, Ballantyne, Packer, & Benckendorff, 2012;Knollenberg, McGehee, Boley, & Clemmons, 2014;Wearing & McGehee, 2013). Therefore, based on the concept of transformative learning, this study investigates how involvement in volunteer tourism can change participants' attitudes and actions toward removing invasive species and, with the involvement of community volunteers, produce a model of citizen action that integrates human resources from inside and outside the community for joint participation in the removal of invasive species.…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, tourism has gradually gained recognition as a learning path (Coghlan & Gooch, 2011;Falk, Ballantyne, Packer, & Benckendorff, 2012;Knollenberg, McGehee, Boley, & Clemmons, 2014;Wearing & McGehee, 2013). Therefore, based on the concept of transformative learning, this study investigates how involvement in volunteer tourism can change participants' attitudes and actions toward removing invasive species and, with the involvement of community volunteers, produce a model of citizen action that integrates human resources from inside and outside the community for joint participation in the removal of invasive species.…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%
“…McGehee and Santos (2005) believed that volunteer tourism may be a consciousness-raising experience for participants, which can lead to changes in their views on society. Additionally, Knollenberg et al (2014) believed that voluntourists use the transformative learning process to seek changes in their views. With regard to the transformative learning process, Coghlan and Gooch (2011) compared the learning and change process in volunteer tourism with Mezirow's (1978) ten phases of transformative learning and found that this process can embody the concept of transformative learning.…”
Section: The Application Of Transformative Learning Theory In Environmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent interview conducted by the author of this Opinion Piece, one organisation director talked of its "cash cow" programmes that offset the more "development-orientated" and "loss-running" projects. It has bothered me ever since that I lacked the succinctness Knollenberg et al (2014) provide to illustrate clearly the interplay between programme design and different types of volunteers in a way that, refreshingly, resists the unending references to either altruism or self-development as definers of volunteer tourists.…”
mentioning
confidence: 99%
“…The paper lays bare the values that are embedded into the evaluation process and offers the work as a dialogic challenge to organisations interested in "greater transparency and accountability" (p. 881). More insight comes in Knollenberg, McGehee, Boley, and Clemmons's (2014) study where they track different modes of Transformative Learning against a useful typology of volunteers, voluntourists and tourists. In a recent interview conducted by the author of this Opinion Piece, one organisation director talked of its "cash cow" programmes that offset the more "development-orientated" and "loss-running" projects.…”
mentioning
confidence: 99%